The cloisters of the Poor Clares in Hungary – an alternative for self-realization of noble women in early modern times (Theatrum historiae, 2011)
The cloisters of the Poor Clares were an alternative to matrimonial life for girls from the higher social strata. Many of them lived in the cloister from early childhood and became nuns mainly at the behest of their parents. The cloistral life restricted them from making social and family contacts; on the other hand it offered some of them the oppor- tunity for self-realization. Abbesses had the possibility to govern the community of women, to manage large properties, and command employees and servants. Some of them worked as nursemaids to children, mistresses of novices or as secretaries who administered the offi- cial paperwork of the cloisters. Some of the nuns devoted their lives to writing books, painting pictures, music and singing. The noble inhabitants of the cloisters remained, never- theless, in contact with their relatives and thus reserved their positions in Hungarian noble society. The life behind the walls of the cloister and possible scandals involving nuns re- sounded in society and attracted general interest.